2012
DOI: 10.1007/s10646-012-0993-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple environmental stressors elicit complex interactive effects in the western fence lizard (Sceloporus occidentalis)

Abstract: Evaluation of multiple-stressor effects stemming from habitat degradation, climate change, and exposure to chemical contaminants is crucial for addressing challenges to ecological and environmental health. To assess the effects of multiple stressors in an understudied taxon, the western fence lizard (Sceloporus occidentalis) was used to characterize the individual and combined effects of food limitation, exposure to the munitions constituent 2,4,6-trinitrotoluene (TNT), and Plasmodium mexicanum (lizard malaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 47 publications
3
51
0
Order By: Relevance
“…However, the effect of such infections on leukocyte profiles is poorly known. Several studies on hematozoan infection in reptiles and amphibians have shown either changes in leukocyte densities or reductions in humoral components of the immune response when infected (Ujvari and Madsen, 2005;Bonadiman et al, 2010;Motta et al, 2011;Shutler and Marcogliese, 2011;McFarland et al, 2012). Although many hematozoan parasites are considered nonpathogenic (Brown et al, 2006;Jacobson, 2007;Stacy et al, 2011), some do result in a variety of physiological, reproductive, and behavioral changes (Schall, 2002;Ujvari et al, 2004;Amo et al, 2005;Ujvari and Madsen, 2005;Vardo-Zalik and Schall, 2008;Motta et al, 2011), and further examination of leukocyte alterations or other immune responses to these infections should clarify this parasite-host biology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the effect of such infections on leukocyte profiles is poorly known. Several studies on hematozoan infection in reptiles and amphibians have shown either changes in leukocyte densities or reductions in humoral components of the immune response when infected (Ujvari and Madsen, 2005;Bonadiman et al, 2010;Motta et al, 2011;Shutler and Marcogliese, 2011;McFarland et al, 2012). Although many hematozoan parasites are considered nonpathogenic (Brown et al, 2006;Jacobson, 2007;Stacy et al, 2011), some do result in a variety of physiological, reproductive, and behavioral changes (Schall, 2002;Ujvari et al, 2004;Amo et al, 2005;Ujvari and Madsen, 2005;Vardo-Zalik and Schall, 2008;Motta et al, 2011), and further examination of leukocyte alterations or other immune responses to these infections should clarify this parasite-host biology.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally infected male S. occidentalis display altered leukocyte profiles, but it is unknown whether this translates to what occurs naturally in this parasitehost system (McFarland et al, 2012), and what changes occur in female lizards has not been examined. We used a case-control study design where naturally infected lizards were paired with noninfected control lizards based on sex, size, tail status, and the presence-absence of ectoparasites and the hemoparasite S. occidentalis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure that the corn oil was homogenously mixed with LCT, the dosing method was set up in steps (Suski et al, 2008;McFarland et al, 2012). LCT was first dissolved in methanol and then dispersed into the corn oil (methanol/oil ¼ 1/9, v/v, total volume 20 mL).…”
mentioning
confidence: 99%